Digitalisasi Kitab Kuning di Pondok Pesantren Annuqayah: Fenomena dan Dampak dalam Transformasi Pembelajaran Islam - Salsabila, Ainan; Thobroni, Imam; Hosnan, Mohammad (JSP: Jurnal Studi Pesantren, 2024)
The digitalization of kitab kuning (Islamic classical texts) represents a significant phenomenon in the globalization era, transforming pesantren learning traditions. The transition from physical kitab kuning to digital applications is not merely a change in learning media but also a transformation of pesantren traditions that sacralize these classical texts. This study aims to analyze the phenomenon of kitab kuning digitalization at Annuqayah Islamic Boarding School, identify underlying factors, and examine its impacts on learning practices. The research employs a descriptive qualitative approach with Thomas Larsson's globalization theory and Edmund Husserl's phenomenological framework. Data were collected through in-depth interviews, participatory observations, and documentation involving kyai (Islamic scholars), santri (students), alumni, and educators at Annuqayah Pesantren Latee. Data analysis utilized the Miles and Huberman model through data reduction, data display, and conclusion drawing stages. Results reveal three user groups based on usage intensity: active users (5-7%), less active users, and non-users. Driving factors include accessibility, academic needs, efficiency, and economic affordability. Inhibiting factors encompass limited facilities, pesantren regulations on electronic device usage, and preferences for physical texts. Positive impacts of kitab kuning digitalization include enhanced learning effectiveness and efficiency, convenient reference access, cost savings, expanded religious literature reach, and paper waste reduction. Negative impacts include potential instant mentality, reduced teacher-student interaction, digital transcription error risks, and loss of spiritual experience in reading physical texts. Despite offering various conveniences, the majority of Annuqayah community maintains the tradition of using physical kitab kuning as their primary learning medium.